The potential toxicity of loop diuretics in patients with cardiovascular complications - Liczner, Grzegorz; Wiciński, Michał; Malinowski, Bartosz; Ozorowski, Mateusz; Długi, Karolina; Rewerski, Sebastian (Journal of Education, Health and Sport, 2018)
A patient with cardiovascular complications is a proper candidate for a diuretic treatment. Here, loop diuretics are the drugs with the greatest strength and time of acting, especially when used in urgent cases like exacerbation of heart failure is overhydration due, pulmonary edema and renal failure. Conducting treatment in Those conditions and the physician should keep in mind and rational dosage of drugs mentioned, the interactions with others and also medicaments patient’s comorbidities. Besides of advantages With diuretic treatment, in still observe Increasing the number of its side effects, Which are the real threat for patients’ life. Key words: loop diuretics, furosemide, torasemide